“A good physician works full-time?” – a mixed-methods study on (mis)conceptions about part-time work in hospitals - Barbara Jarmila Germann; Julia Frey; Alain Soltermann; Janna Küllenberg (Swiss Medical Weekly)
STUDY AIMS: While part-time employment is commonly discussed as a way to recruit and retain physicians, the average workload of hospital physicians has barely decreased in the past decade, and hospitals face persistent difficulties in adopting part-time work. This study aims to examine the attitudes of hospital physicians across various specialties and positions towards part-time employment, and to identify factors that hinder or facilitate the successful implementation of part-time arrangements in hospital settings.